1998
DOI: 10.1007/bf01417673
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for the evaluation of travel techniques for immersive virtual environments

Abstract: We present a framework for the analysis and evaluation of travel, or viewpoint motion control, techniques for use in immersive virtual environments (VEs). In previous work, we presented a taxonomy of travel techniques and a set of experiments mapping parts of the taxonomy to various performance metrics. Since these initial experiments, we have expanded the framework to allow evaluation of not only the effects of different travel techniques, but also the effects of many outside factors simultaneously. Combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 28 publications
1
71
0
1
Order By: Relevance
“…Motion cueing has also been widely studied, showing that it can enhance overall usability and user experience [21]- [23], enhance spatial perception and orientation [22], and reduce motion sickness [35]. Harris and colleagues [34] found passive physical motion, i.e., remaining inactive while the simulation moves the user, evokes an enhanced sensation of motion, but also tends to dominate other cues; and they found a complete match between visual and vestibular cues was not required to help induce self-motion.…”
Section: Motion Cueingmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion cueing has also been widely studied, showing that it can enhance overall usability and user experience [21]- [23], enhance spatial perception and orientation [22], and reduce motion sickness [35]. Harris and colleagues [34] found passive physical motion, i.e., remaining inactive while the simulation moves the user, evokes an enhanced sensation of motion, but also tends to dominate other cues; and they found a complete match between visual and vestibular cues was not required to help induce self-motion.…”
Section: Motion Cueingmentioning
confidence: 99%
“…Interfaces that utilize spatial updating, also known as physical navigation interfaces, have been shown to increase usability and spatial orientation [21]- [23]. In terms of self-motion, researchers investigating the integration of visual and vestibular sensory cues found that visual and non-visual cues are by themselves sufficient, but together are stronger in signaling self-motion [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…The VR motion type shares common characteristics with the component of input conditions, i.e., the way in which the technique specifies VR motion. Moreover, in an expanded version of Bowman et al's framework [16], the size of the environment was considered significant for the performance of the VR locomotion technique, a characteristic represented in the theme of VR interaction space. Arns' work [17] on extending Bowman et al's taxonomy and introducing the concept of physical and virtual interaction regarding the rotation of the virtual environment and the translation of the user's viewpoint presents common elements with the interaction type theme.…”
Section: Vr Locomotion Techniques and Interaction Aspectsmentioning
confidence: 99%
“…Moreover, many studies have been done on 3D interaction techniques using hand manipulation, such as the silk cursor [24], ray-casting interaction [3], go-go interaction [20], IntenSelect [8], body-relative interaction [14], image plane interaction [19], and scaled manipulation [6]. These techniques use a handheld device such as a stylus to manipulate a virtual object.…”
Section: Related Workmentioning
confidence: 99%